Children's Aged 9 - 12 Years Knowledge About Toothbrushes Cleanliness - Henri Hartman; Gina Isabelina Suseno; Marlin Himawati (Jurnal EduHealth, 2022)
The toothbrush is one of the tools that is used to clean teeth and mouth from microorganisms that cause dental infections. Tooth brushing alone was not enough to maintain teeth and mouth hygiene but also maintaining the cleanliness of the used toothbrush also needs to be considered because toothbrushes that were not properly stored and treated well enough could be contaminated by microorganisms. This research and identity to identify the knowledge of 9-12 years old children about toothbrush maintenance. This research was done as a descriptive study. The sample of this research was 50 children aged from 9 to 12 years old who live in Cicaheum, Bandung, selected randomly. We used some online questionnaires to the children about toothbrush maintenance and storage as the research instrument. The data of this research were presented in the form of a table of characteristics of the subject's knowledge level. The result showed that the knowledge of children aged 9 to 12 years old in Cicaheum towards toothbrush maintenance was relatively high, with the number of 23 children (46.00%).